Low levels of IgM antibodies recognizing oxidation-specific epitopes are associated with human non-alcoholic fatty liver disease. Issue 1 (December 2016) - Hendrikx, Tim; Watzenböck, Martin; Walenbergh, Sofie; Amir, Shahzada; Gruber, Sabrina; Kozma, Maria; Grabsch, Heike; Koek, Ger; Pierik, Marieke; Staufer, Katharina; Trauner, Michael; Kalhan, Satish C.; et al.
Abstract Background Lipid oxidation of membrane phospholipids is accompanied by the formation of oxidation-specific epitopes (OSE). These epitopes are recognized by specific antibodies and represent danger-associated molecular patterns that are generated during chronic inflammatory processes. In a murine model for hepatic inflammation during non-alcoholic fatty liver disease (NAFLD), increased antibody levels targeting OSE were found to be protective. Here, our aim was to determine an association between OSE-specific antibody titers and NAFLD in humans. Methods IgM and IgG levels with specificity for various OSE were assessed in the plasma of patients with NAFLD (n =  71) and healthy controls (n =  68). Antibody titers were comprehensively analyzed in patients with NAFLD after classification by histological evaluation of liver biopsies. Statistical analysis was performed to determine significant correlations and odds ratios. To study the specificity for NAFLD, plasma antibody titers were measured in patients with hepatitis C (n  = 40) and inflammatory bowel disease (n =  62). Results IgM titers against OSE were lower in patients with NAFLD compared to controls. Further biopsy-based classification of patients with NAFLD did not show any difference in IgM levels. Plasma IgM titers towards the P1 mimotope demonstrated an inverse correlation with markers for obesity, systemic inflammation, and liver damage. In contrast, hepatitis C and increased disease activity during inflammatory bowel disease was not associated with reduced IgM titers. Conclusions Our data highlight the importance of immune recognition of OSE by IgM antibodies in the pathophysiology of NAFLD.